2009
DOI: 10.1186/1750-9378-4-s1-s3
|View full text |Cite
|
Sign up to set email alerts
|

Microarray comparison of prostate tumor gene expression in African-American and Caucasian American males: a pilot project study

Abstract: African American Men are 65% more likely to develop prostate cancer and are twice as likely to die of prostate cancer, than are Caucasian American Males. The explanation for this glaring health disparity is still unknown; although a number of different plausible factors have been offered including genetic susceptibility and gene-environment interactions. We favor the hypothesis that altered gene expression plays a major role in the disparity observed in prostate cancer incidence and mortality between African A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 7 publications
(6 reference statements)
5
49
0
Order By: Relevance
“…Similar findings to the Glasgow studies are apparent in studies aiming to determine why men of African American (AA) race are two to three times more likely to die from prostate cancer that European Americans (EA) (Horner et al 2009). Gene expression microarray studies of prostate cancer tissues from AA and EA men have consistently shown overexpression of gene sets involving inflammation pathways in AA samples (Powell et al 2013;Reams et al 2009;Wallace et al 2008). This includes differentially expressed gene clustering in pathways involved in immune response, interleukins, and cytokine signaling and overexpression of specific genes such as IL-6, IL-8, and IL-1β (Powell et al 2013;Reams et al 2009;Wallace et al 2008).…”
Section: Additional Innate Immune Cells In Prostate Cancermentioning
confidence: 98%
“…Similar findings to the Glasgow studies are apparent in studies aiming to determine why men of African American (AA) race are two to three times more likely to die from prostate cancer that European Americans (EA) (Horner et al 2009). Gene expression microarray studies of prostate cancer tissues from AA and EA men have consistently shown overexpression of gene sets involving inflammation pathways in AA samples (Powell et al 2013;Reams et al 2009;Wallace et al 2008). This includes differentially expressed gene clustering in pathways involved in immune response, interleukins, and cytokine signaling and overexpression of specific genes such as IL-6, IL-8, and IL-1β (Powell et al 2013;Reams et al 2009;Wallace et al 2008).…”
Section: Additional Innate Immune Cells In Prostate Cancermentioning
confidence: 98%
“…The most recent study by Reams et al compared gene expression profiling in tumors with a Gleason's score of 6 from AfricanAmerican males to prostate tumors in European-American males (23). This study also showed that the gene ontology terms prevalent in African-American male prostate tumor/ normal ratios included interleukins, progesterone signaling, chromatin-mediated maintenance and myeloid dendritic cell proliferation (23).…”
Section: Introductionmentioning
confidence: 82%
“…The study mostly detected differential expression of immune responsive genetic programs in African-American as compared to European-American patients that offer potentially important leads for understanding the disease (22). The most recent study by Reams et al compared gene expression profiling in tumors with a Gleason's score of 6 from AfricanAmerican males to prostate tumors in European-American males (23). This study also showed that the gene ontology terms prevalent in African-American male prostate tumor/ normal ratios included interleukins, progesterone signaling, chromatin-mediated maintenance and myeloid dendritic cell proliferation (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reams et al [33] observed that the transcription elongation factor A-like 7 (TCEAL 7) expression in PCa tumor and in non-tumor tissue was higher in EA compared to AA men. The TCEAL7 gene modulates transcription in a promoter context-dependent manner.…”
Section: Biological (Functional) Differences In Prostate Tumors Ofmentioning
confidence: 99%